Great writing 4 : Great essays - Folse, Keith S.; Muchmore-Vokoun, April; Solomon, Elena Vestri (Boston Cengage Learning, 2010)
The Great Writing series uses clear explanations and extensive practical activities to help students write great sentences, paragraphs, and essays. Each book contains a wide variety of writing models in carefully selected rhetorical styles that provide practice in working with the writing process to develop a final piece of writing. Great Writing 4: Great Essays shows students how to write effective essays and provides practice in rhetorical patterns.
Keywords: Ngôn ngữ Anh